2014
DOI: 10.1037/neu0000055
|View full text |Cite
|
Sign up to set email alerts
|

Simulating category learning and set shifting deficits in patients weight-restored from anorexia nervosa.

Abstract: Objective To examine set shifting in a group of women previously diagnosed with anorexia nervosa who are now weight-restored (AN-WR) and then apply a biologically-based computational model (Competition between Verbal and Implicit Systems; COVIS) to simulate the pattern of category learning and set shifting performances observed. Method Nineteen AN-WR women and 35 control women (CW) were administered an explicit category learning task that required rule acquisition and then a set shift following a rule change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 63 publications
(100 reference statements)
1
34
0
Order By: Relevance
“…As mentioned earlier, the COVIS model of procedural learning, which also only includes a direct pathway, is nevertheless consistent with a wide variety of data (Ashby et al, 2007; Crossley et al, 2013, 2014; Filoteo et al, 2014; Hélie et al, 2012; Valentin et al, 2014). Following the computational cognitive neuroscience simplicity heuristic (Ashby & Helie, 2011), we do not include structure unless it is critical for function or is required by existing data.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…As mentioned earlier, the COVIS model of procedural learning, which also only includes a direct pathway, is nevertheless consistent with a wide variety of data (Ashby et al, 2007; Crossley et al, 2013, 2014; Filoteo et al, 2014; Hélie et al, 2012; Valentin et al, 2014). Following the computational cognitive neuroscience simplicity heuristic (Ashby & Helie, 2011), we do not include structure unless it is critical for function or is required by existing data.…”
supporting
confidence: 81%
“…Stimuli are associated with categorization responses via changes in synaptic strength at cortical-striatal synapses between pyramidal neurons in visual association areas and medium spiny neurons in the striatum. Although COVIS accounts for an impressive variety of data (e.g., Ashby, Ennis, & Spiering, 2007; Crossley, Ashby, & Maddox, 2013, 2014; Filoteo et al, 2014; Hélie, Paul, & Ashby, 2012; Valentin, Maddox, & Ashby, 2014), because it postulates only one stage of learning, it predicts either worse transfer performance in II tasks after a full reversal than after a switch to new categories, or a switch to suboptimal declarative strategies during reversals.…”
Section: A New Biologically Detailed Model Of Procedural Category Leamentioning
confidence: 99%
“…Many individuals with AN respond in a fearful or avoidant manner to salient rewards, such as highly palatable food, rather than experiencing pleasure, and computational modeling studies show increased learning from punishment as opposed to reward in RAN (81). We have previously proposed that individuals with AN may have an intrinsic sensitivity to coding salient stimuli, such as food, as aversive or risky, rather than rewarding, that overrides the influences of hunger (82).…”
Section: Discussionmentioning
confidence: 99%
“…The idea is to fit the model to data from both groups and examine which parameters need to be manipulated to account for the group differences. When Filoteo et al (2014) followed this strategy, they found that the model gave good fits to all aspects of both data sets under the following conditions. First, the AN group showed hypersensitivity to negative feedback, which accounted for the hyper-learning on the first category structure (but did not cause the model to predict hyper-learning on subsequent structures).…”
Section: Clinical Applications Of Quantitative Modeling Of Category Lmentioning
confidence: 99%
“…Accuracy (proportion correct) for weight restored Anorexic patients (AN-WR) and control women (CW) groups (error bars are standard error of the mean) in the study by Filoteo et al (2014).…”
Section: Figurementioning
confidence: 99%